Pengembangan Media Ajar Interaktif Berbantuan Microsoft Powerpoint Menggunakan Add-In Classpoint Pada Mata Pelajaran Komputer Akuntansi Kelas XI AKL - Diah Pramesti; Rochmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This development research aims to produce an interactive teaching media product assisted by Microsoft Powerpoint using the Classpoint add-in in the Accounting Computer subject class XI AKL. Another goal is to find out the process of developing teaching media, the feasibility of teaching media, and the response of students to the developed teaching media. This study uses a type of R&D (Research and Development) research with the ADDIE development model which consists of 5 stages, namely Analyse, Design, Develop, Implement, and Evaluate. The test subjects of this study are grade XI AKL students from SMK YPM 11 Wonoayu. The results of this study show the results of the material expert test by the Lecturer of the Faculty of Economics and Business and the Teacher of the Accounting Computer subject of SMK YPM 11 Wonoayu which is said to be very feasible with an average percentage of 88.13%, while the results of the media expert test by the Lecturer of the Faculty of Economics and Business are said to be very feasible with an average presentation of 88.89%. The response from students of class XI AKL SMK YPM 11 Wonoayu to the interactive teaching media developed received an average of 97.99% which was included in the category of very understanding. From the average results of the above percentage, it can be said that interactive teaching media assisted by Microsoft Powerpoint using the Classpoint add-in in the Accounting Computer subject class XI AKL is very feasible and can be applied to learning in the classroom